Identifying clinical criteria to predict Type 1 diabetes, as defined by absolute insulin deficiency: a systematic review protocol. Issue 6 (28th December 2012) - Shields, Beverley M; Peters, Jaime L; Cooper, Chris; Powell, Roy J; Knight, Bridget A; Hyde, Christopher; Hattersley, Andrew T
Abstract : Introduction: Management of a patient's diabetes is entirely dependent upon the type of diabetes they are deemed to have. Patients with Type 1 diabetes are insulin deficient so require multiple daily insulin injections, whereas patients with Type 2 diabetes still have some endogenous insulin production so insulin treatment is only required when diet and tablets do not establish good glycaemic control. Despite the importance of a correct diagnosis, classification of diabetes is based on aetiology and relies on clinical judgement. There are no clinical guidelines on how to determine whether a patient has Type 1 or Type 2 diabetes. We aim to systematically review the literature to derive evidence-based clinical criteria for the classification of the major subtypes of diabetes. Methods and analysis: We will perform a systematic review of diagnostic accuracy studies to establish clinical criteria that predict the subsequent development of absolute insulin deficiency seen in Type 1 diabetes. Insulin deficiency will be determined by reference standard C-peptide concentrations. Synthesis of criteria identified will be undertaken using hierarchical summary receiver operating characteristic curves. Ethics and dissemination: As this is a systematic review, there will be no ethical issues. We will disseminate results by writing up the final systematic review and synthesis for publication in a peer-reviewed journal and will present at national and international diabetes-related meetings.